Representasi Kepribadian Muslimah Dalam Novel Rissa Sebuah Pilihan Hidup Karya Larissa Chou (Kajian Feminimisme) - Sumana, Sumana; Wardiah, Dessy; Missriani, Missriani (Indonesian Research Journal on Education, 2023)
Feminism is a school that fights for the rights of women, women must be able to do somethingwithout men and women can beat men. In this case, it means that women demand gender equality between women and men. Feminism also justifies the awareness of the gender injustice that afflicts women in the family and in society. The purpose of this study is to find out how the analysis of Muslim personality in the study of feminism in the novel Rissa a life choice by Larissa Chou which includes injustice and inequality in women. Risaa's novel A Choice of Life tells of a woman who fights for her desire in choosing a belief or becoming a convert, Larissa is a big body from a broken home family, Papa and Mama Larissa divorced since childhood, but Larissa has a very good personality, even she has to become a convert and is a Muslim. in his life he understands that actually every human being has a life choice that must be implemented even accepted despite the many contradictions about it.